2017
DOI: 10.1159/000479388
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Peanut Allergens Ara h 2 and Ara h 6 in Human Breast Milk: Development of 2 Sensitive and Specific Sandwich ELISA Assays

Abstract: Background: Little is known about breast milk as a vehicle for tolerance development or sensitization to peanuts very early in life. Thus, well-characterized and highly sensitive detection systems for the reliable determination of peanut allergens in breast milk are mandatory. Methods: For the quantification of the marker allergens Ara h 2 and Ara h 6 in the low nanogram per milliliter range in breast milk samples of a German cohort, sensitive and highly specific sandwich ELISAs were optimized and validated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…As BLG detection relied on the use of an immunometric assay, BLG might not be detectable in the former milks due to a masking effect of specific antibodies present in the breastmilk and/or the presence of BLG mainly as immune complexes. The fact that not all mothers were found to be excretors in various studies might result from the same masking effect (7)(8)(9)(10)(11)(12)(14)(15)(16)(17). This might then imply that all mothers are actually excretors of allergens in their BM, but as a free and/or complexed form depending on the levels of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As BLG detection relied on the use of an immunometric assay, BLG might not be detectable in the former milks due to a masking effect of specific antibodies present in the breastmilk and/or the presence of BLG mainly as immune complexes. The fact that not all mothers were found to be excretors in various studies might result from the same masking effect (7)(8)(9)(10)(11)(12)(14)(15)(16)(17). This might then imply that all mothers are actually excretors of allergens in their BM, but as a free and/or complexed form depending on the levels of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, breastmilk might influence immune system development via the transfer of various immunomodulatory molecules directly acting on the epithelial and immune system, or acting via the microbiota, such as regulatory/proinflammatory cytokines, miRNA, immunoglobulins, nutrients, but also metabolic products from the microbiota (2)(3)(4)(5). Human breastmilk also contains food antigens, which have been ingested by the mother (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). While the factors controlling food antigen shedding in breastmilk are poorly identified, the excretion of food antigens, at low doses and over a long period of time after ingestion (>24 h), appears as a natural process.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoassays generally remain the method of choice in detecting food allergens in complex food matrices due to their high sensitivity, specificity and simplicity, and have also been applied to the detection of peanut allergens such as Ara h 6 in human biological samples. 10,11,32,33 However, endogenous proteins, particularly in the blood, With this strategy, we were successful in detecting Ara h 6 in serum samples collected from both healthy and allergic volunteers following ingestion of much lower amounts of peanut (<1 g) than that previously reported in the literature. Actually, we were able to detect Ara h 6 following consumption of 300 mg peanut protein (equivalent to ~1½ peanuts) by all healthy volunteers, with Ara h 6 detection increasing in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
“…3 Food proteins have also been detected at low levels in placental tissue [4][5][6] and in breastmilk. [7][8][9][10][11] The transfer of food antigens may be enhanced in diseases where intestinal barrier integrity is impaired, such as coeliac disease 12 and in subjects with underlying food allergy, [13][14][15][16] although data are limited. Intestinal permeability is not predictive of food allergy, 17 but may play a role in specific conditions such as wheat-dependent exercise-induced anaphylaxis.…”
Section: Absorption Of Non-digested Dietary Antigens and Their Passagementioning
confidence: 99%
“…Moutsoglou and Dreskin [63] investigated the role of long-lived antibody-secreting cells in peanut allergy and the potential of the proteasomal inhibitor bortezomib as a therapy in this context. While they found that bortezomib decreased long-lived anti-peanut IgE in mice, a correlative decrease in allergic symptoms was not observed.…”
Section: Food Allergymentioning
confidence: 99%